2017
DOI: 10.1145/3072959.3073672
|View full text |Cite
|
Sign up to set email alerts
|

Hiding of phase-based stereo disparity for ghost-free viewing without glasses

Abstract: When a conventional stereoscopic display is viewed without stereo glasses, image blurs, or 'ghosts', are visible due to the fusion of stereo image pairs. This artifact severely degrades 2D image quality, making it difficult to simultaneously present clear 2D and 3D contents. To overcome this limitation (backward incompatibility), here we propose a novel method to synthesize ghost-free stereoscopic images. Our method gives binocular disparity to a 2D image, and drives human binocular disparity detectors, by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…An elevation of perceived contrast may be observed when stereoscopic images are artificially synthesized from 2D images by adding binocular disparity information (e.g. Fukiage, Kawabe, and Nishida, 2017 ). Our measurements using the method of constant stimuli indicated that the perceived contrast was 1.1 times higher at 1 degree uncrossed disparity.…”
Section: Discussionmentioning
confidence: 99%
“…An elevation of perceived contrast may be observed when stereoscopic images are artificially synthesized from 2D images by adding binocular disparity information (e.g. Fukiage, Kawabe, and Nishida, 2017 ). Our measurements using the method of constant stimuli indicated that the perceived contrast was 1.1 times higher at 1 degree uncrossed disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Perception and analysis: Incosistent stereoscopic images result in undesirable perceptual artifacts [13], often called 'ghosting'. This could either be caused by incompatible stereoscopic content [25] or due to imperfections in the display system.…”
Section: Auto-multiscopic Displaysmentioning
confidence: 99%
“…Fukiage et al proposed a method for a conventional 3D glasses stereoscopic display to synthesize ghost-free stereoscopic images for no-glasses observers [3]. This method gives binocular disparity to an original 2D image and drives human binocular disparity detectors by the addition of a quadrature phase pattern.…”
Section: Hidden Stereo Technologymentioning
confidence: 99%
“…As a result, when the observer's viewpoint changing, a good image quality image and a bad image quality image change suddenly and smooth transition of image quality could not be reproduced. In order to solve this problem, we have developed and in this paper propose a method to generate the output images of linear blending by using 'hidden stereo' technology [3] that provides disparity by the addition of a quadrature-phase pattern. Image quality evaluations using PSNR (peak signal-to-noise ratio) and SSIM (structural similarity) show that the method effectively reduces image quality variation and makes it possible to further reduce the number of projectors needed without reducing the image quality.…”
Section: Introductionmentioning
confidence: 99%